PENINGKATAN MAWAS DIRI KONSUMEN MENGGUNAKAN PRODUK BERLABEL HALAL - Mardiyono, Mardiyono (Jurnal Cakrawala Hukum, 2017)
The large quantity of goods and service produced by businessmen required customers to be more careful eitherto choose or to use the product, especially to theproduct with label ‘kosher.’The action to keep on guard theproduct produced by businessmen did not need special clarification, not only in the practice but it also neededto pay attention on the regulation to avoid loss in using it. Once the customer did a careless thing, he or shewould get an effect later. Customers had got protection for fourteen years based on the regulation No 8 year1999. However, in progress, itrequired customers, stated in regulation as the last customers, to be more carefulespecially in consuming foreign product. Normatively, the kosher of this product had to be tested.